Primary Vesical Actinomycosis in a 23-Year-Old Man - Tevfik Ziypak; Senol Adanur; Fatih Ozkaya; Muhammet Calık; Ozkan Polat; Yilmaz Aksoy; Isa Ozbey (Case Reports in Urology)
Introduction. Actinomycosis can affect any organ of the body, although cutaneous fistulas are common in actinomycotic infections, and other organs such as the bladder are only rarely involved. Case Presentation. Herein we report and discuss a young male patient with primary vesical actinomycosis. A 23-year-old man was hospitalized complaining of intermittent gross hematuria over a 6-month duration. The patient underwent a cystoscopic examination under general anesthesia; an edematous, hyperemic, wide-based mass, which protruded from the dome of the bladder, was seen and incompletely resected. The histopathological examination of the material showed Actinomyces organisms surrounded by inflammation and a photomicrograph showed the microorganism. After confirmation of bladder actinomycosis, the patient received penicillin. A CT scan of the abdomen and pelvis showed no evidence of the mass at the postoperative 6th month. Cystoscopic examination showed complete healing of the transurethral resection area at the dome of the bladder. Conclusion. In conclusion, we believe that the gold standard treatment for vesical actinomycosis should include the combination of a transurethral resection of the mass and long-term penicillin treatment.